Are Feedback and Reinforcement Questions in The Recitation Program Able to Improve Students' Conceptual Mastery? - Rahim, Handy Faishal; Biruni, Iqbal Bilgrami; Romansyah, Teddy Amin; Hidayat, Arif Hidayat; Sutopo, Sutopo (Universal Education Jurnal Teaching and Learning, 2024)
One of the primary goals of physics education is to achieve a solid conceptual understanding among learners. This conceptual understanding, which enables students to address the challenges they encounter effectively, is conceptual mastery. A higher level of conceptual mastery correlates with an increased capacity for students to tackle everyday problems successfully. This study aims to identify the improvement of students' conceptual mastery through a multi-representation-based recitation program accompanied by feedback and reinforcement questions. The method used in this research is descriptive quantitative, carried out on 36 students of the Physics Undergraduate Study Program. The recitation program is multi-representational and multi-context-based, which contains reinforcement questions and feedback used by students outside of lecture hours to help master the concepts obtained in class. The results showed the mastery of concepts of momentum and impulse students increased, indicated by the transition of student's answers and the average of students from 30.8 to 52.8. The increase in students' mastery of concepts is shown in questions in the context of determining impulses in related problems and the conservation of momentum in related problems. The multi-representation and multi-context presented in the recitation program and pretest and posttest questions affect students' mastery of concepts in solving problems.